P1739 Diameter of the pulmonary artery in relation to the ascending aorta: a promising parameter for the diagnosis of pulmonary hypertension. (17th January 2020) - Schneider, M; Ran, H; Pistritto, A M; Gerges, C; Heidari, H; Hengstenberg, C; Bergler-Klein, J; Lang, I; Binder, T; Goliasch, G
Abstract: Background: Pulmonary hypertension (PH) is a disease with significant morbidity and mortality. The first imaging modality in the diagnostic algorithm is transthoracic echocardiography (TTE). Despite significant technological advances in recent years, there are still patients with PH who are missed by TTE. The pulmonary artery to ascending aorta ratio (PA/Ao-R) has been evaluated in cardiac magnetic resonance (CMR) and computed tomography (CT) studies. The ratio was able to detect patients with PH, it correlated with hemodynamics, and it was predictive for mortality. We sought to evaluate the diagnostic accuracy of PA/Ao-R measured by TTE in the detection of PH. Methods: We evaluated consecutive patients who received quasi-simultaneous transthoracic echocardiography and right heart catheterization (RHC) for evaluation of pulmonary hypertension between July 2015 and July 2016. Results: A total of 84 patients fulfilled the inclusion criteria, 47 were female, mean age was 65 years. Median PA/Ao-R was 0.8 (Q1;Q3 0.69;0.94). Seventy patients had PH (median mean pulmonary artery pressure (mPAP) was 35.5 mmHg, Q1;Q3 27;47). The area under the curve for the diagnosis of PH via PA/Ao-R was 0.853. A cut-off of 1 was chosen for further analysis. Sensitivity for the diagnosis of PH was 100%, specificity was 23%. PA/Ao-R correlated with mPAP (r = 0.65, p < 0.001), and pulmonary vascular resistance (r = 0.68, p < 0.001). In the subgroup of patients with PH, those patients with a PA/Ao-R of ≥1 had significantly (p < 0.001) higher pulmonary pressures than those below, with a mean mPAP of 53 mmHg as compared to 38.5 mmHg. Conclusion: PA/Ao-R correlates with mPAP. A ratio of ≥1 should prompt suspicion for the presence of PH. PA/Ao-R should be reported in every patient who is evaluated for PH.